STRATEGI GURU DALAM MENGELOLA SARANA DAN PRASARANA PENDIDIKAN DALAM MENINGKATKAN KONSENTRASI BELAJAR SISWA KELAS V DI SEKOLAH DASAR NEGERI 50 SUKA DAMAI KECAMATAN TEBAS TAHUN PELAJARAN 2023-2024 - Atma Sri Utami; Suhari; Poniam (CV. Adiba Aisha Amira, 2026)
The purpose of this study is to describe: 1) Learning planning from Teacher Strategies in managing educational facilities and infrastructure to improve the learning concentration of fifth-grade students at Public Elementary School 50 Suka Damai, Tebas District, in the 2023-2024 academic year. 2) Implementation of learning planning from Teacher Strategies in managing educational facilities and infrastructure to improve the learning concentration of fifth-grade students at Public Elementary School 50 Suka Damai, Tebas District, in the 2023-2024 academic year. 3) Obstacles and solutions to learning planning from Teacher Strategies in managing educational facilities and infrastructure to improve the learning concentration of fifth-grade students at Public Elementary School 50 Suka Damai, Tebas District, in the 2023-2024 academic year. This study uses a qualitative approach and a qualitative descriptive research type. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. (1) The Facilities and Infrastructure Arrangement Plan at Public Elementary School 50 Suka Damai already has the necessary learning tools, but the number still needs to be increased. (2) The Teaching Management Plan of Suka Damai 50 Public Elementary School, the school has a strong commitment to ensuring the quality of teaching through careful planning and continuous evaluation. (3) Obstacles and Solutions used by Teachers in Managing Educational Facilities and Infrastructure in Improving the Learning Concentration of Fifth Grade Students at Suka Damai 50 Public Elementary School, namely the Lack of Teacher Understanding and Application of the Importance of Class Management and lack of focus.